(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This research analyzes the effect of both intrinsic and extrinsic motivation to the employees’ performance in Shakti Hotel Bandung. The samples used in this research are 80 employees who are analyzed by using validity test, reliability test, multiple linear regression analysis, determination analysis, and hypothesis test with SPSS 23 program. The result of validity test shows that the instruments are above 0.3 of reliability test result by using Cronbach’s Alpha that is above 0.60. The partial correlation test of each variable has a different effect where the intrinsic motivation has positive and low effect, while the extrinsic motivation has positive and strong effect. The result of multiple correlation analysis shows that there is positive and strong correlation simultaneously between intrinsic and extrinsic motivation to the employees’ performance. According to the coefficient analysis of determination, both the independent variables contribute 47.5% to the employee’s performance. Meanwhile, the hypothesis test shows that both intrinsic and extrinsic motivation affects positively to the employees’ performance in Shakti Hotel Bandung.